Analisis Faktor yang Berhubungan Dengan Tingkat Kepuasan Kerja Perawat di Puskesmas - Mukhlis Mukhlis; Masri Masri; Abqariah Abqariah; Khairul Fahmi (Public Health Journal, 2026)
Service quality is the main aspect of service delivery at the Community Health Center (Puskesmas). Service quality that is well maintained by the Community Health Center will provide satisfaction to patients and satisfaction to healthcare workers, one of whom is nurses. Nurses contribute greatly to providing safe care. Therefore, nurses must have job satisfaction so that every task they perform can be carried out comfortably and safely. The purpose of this study was to determine the factors associated with the level of nurses' job satisfaction at the Simpang Tiga Community Health Center, Pidie Regency. This study was analytical with a cross-sectional study design. The population and sample in this study were all nurses at the Simpang Tiga Community Health Center, totaling 37 people. This study was conducted from July 1–5, 2024. The sampling technique used was total sampling. Data were collected using a questionnaire. The results of the univariate analysis showed that the majority of nurses were satisfied with their jobs (81.1%), the majority of nurses had inadequate salaries (51.4%), the majority had supportive interpersonal relationships (81.1%), and the majority had vocational education (73%). The results of the bivariate analysis showed that there was a relationship between salary and nurses' job satisfaction (P = 0.005), there was a relationship between interpersonal relationships and nurses' job satisfaction (P = 0.015), and there was no relationship between education and nurses' job satisfaction (P = 0.086). It is recommended that respondents improve cooperation, mutual trust, and communication among nurses, both with supervisors and with fellow nurses.